2016
DOI: 10.1007/s10482-016-0746-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of restriction enzyme pattern analysis and full gene sequencing of 16S rRNA gene for Nocardia species identification, the first report of Nocardia transvalensis isolated of sputum from Iran, and review of the literature

Abstract: Nocardial infections occur in different organs of the body and are common in immune disorder diseases of individuals. The aim of this study was to assess Nocardia species identification by phenotypic tests and molecular techniques applied to nocardiosis in Iranian patients. In the current study, various clinical samples were collected and cultured on conventional media and using the paraffin baiting method. Various phenotypic tests were performed. For accurate identification at the species level, restriction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The lungs are the primary site of Nocardia cyriacigeorgica infection (11). Neocardia cyriageorgica was originally thought to belong to NAC, due to differences in antibiotic susceptibility patterns; now it is considered a separate entity with the advent of newer molecular diagnostic techniques such as 16s-rRNA gene (12) or matrix-assisted laser depression. It is reported that ionization time to combat invasive infection caused by N.cyriageorgica is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs are the primary site of Nocardia cyriacigeorgica infection (11). Neocardia cyriageorgica was originally thought to belong to NAC, due to differences in antibiotic susceptibility patterns; now it is considered a separate entity with the advent of newer molecular diagnostic techniques such as 16s-rRNA gene (12) or matrix-assisted laser depression. It is reported that ionization time to combat invasive infection caused by N.cyriageorgica is increasing.…”
Section: Discussionmentioning
confidence: 99%
“…N. asteroides was the most frequently recovered, followed by N. farcinica and N. cyriacigeorgica (9). Other reports have shown N. cyriacigeorgica, N. asteroides complex, N. nova complex, N. otitidiscaviarum, and N. transvalensis in Iran (10)(11)(12)(13). The prevalence of Nocardial infections in another study was 5.28% (6).…”
Section: Introductionmentioning
confidence: 86%
“…Then based on the abstract evaluation, 55 articles were excluded (3 review articles, 27 case reports, 8 letters to the editor, and 17 were related to non-clinical Nocardia specimens). So, according to quality assessment criteria and inclusion/exclusion criteria data, a remaining 20 most-related articles were included in present study [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Among 20 articles involving a total of 338 Nocardia isolates, the prevalence of Nocardia spp.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%